1995
DOI: 10.1007/bf02191874
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and depression in the oldest old in a German and in U.S. communities

Abstract: Data on cognitive impairment in the oldest old is reported comparing two different samples, one in Munich, Germany, and the other in the United States (Epidemiologic Catchment Area [ECA] study). In both studies the Mini Mental State Examination (MMSE) was used for assessing cognitive impairment. The Munich sample consisted of 402 and the ECA sample of 827 very old people aged 85 years and above. The results indicate that approximately 40% of each sample scored below 24 points in the MMSE indicating at least mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…It is because of the social relationship and education, above all, the biological differences between men and women (Chen et al , ). While gender differences are not always demonstrated (Mcdougall et al , ; Snowdon and Lane, ), not even among the very old (aged >75–>85 years) (Skoog, ; Fichter et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…It is because of the social relationship and education, above all, the biological differences between men and women (Chen et al , ). While gender differences are not always demonstrated (Mcdougall et al , ; Snowdon and Lane, ), not even among the very old (aged >75–>85 years) (Skoog, ; Fichter et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…31 Among the elderly, dysthymia affects 2% to 6% of population. [32][33][34] In the present study, the prevalence of dysthymia found was 5.5%, indicating that the condition presents itself with significant frequency in older adults in this region and that it is consistent with percentages found in studies of other regions. 32 With regard to the other factors associated with a higher prevalence of dysthymia, which were the male gender, a history of smoking and the presence of hypertension, the results of the present study corroborate other studies.…”
Section: Discussionsupporting
confidence: 91%
“…One major consequence of an ongoing demographic aging is a substantial increase in the occurrence of dementia [13,32], in Germany as well as in other countries. Different studies conclude that senile dementia is strongly age-related [28,33,34], Depending on the specific instruments to diagnose dementia, the prevalence rates of dementia among the oldest old is esti mated to be between 16 and 43% in Germany [28], With respect to this observation the low frequency of dementia among elderly hospital patients is remarkable. The low prevalence rate of dementia in our sample may be seen as an indirect sign of a general underestimation of this diag nosis, which has already been described in the literature [10,11].…”
Section: Discussionmentioning
confidence: 99%